Response surface methodology for optimization of nitrocellulose preparation from nata de coco bacterial cellulose for propellant formulation - Nursyafiqah Jori Roslan; Siti Hasnawati Jamal; Jahwarhar Izuan Abdul Rashid; Mohd Nor Faiz Norrrahim; Keat Khim Ong; Wan Md Zin Wan Yunus (Heliyon, 2024)
Nitrocellulose (NC) has garnered significant interest among researchers due to its versatile applications, contingent upon the degree of nitration that modifies the cellulose structure. For instance, NC with a high nitrogen content, exceeding 12.5%, finds utility as a key ingredient in propellant formulations, while variants with lower nitrogen content prove suitable for a range of other applications, including the formulation of printing inks, varnishes, and coatings. This communication aims to present the outcomes of our efforts to optimize the nitration reaction of bacterial cellulose to produce high-nitrogen-content NC, employing the response surface methodology (RSM). Our investigation delves into the influence of the mole ratio of sulfuric and nitric acids, reaction temperature, and nitration duration on the nitrogen content of the resultant products. Utilizing a central composite design (CCD), we identified the optimal conditions for NC synthesis. Analysis of variance (ANOVA) underscored the substantial impact of these reaction conditions on the percentage of nitrogen content (%N) yield. By implementing the predicted optimal conditions—namely, a H2SO4:HNO3 mole ratio of 3:1, a reaction temperature of 35 °C, and a reaction period of 22 min—we successfully produced NC with a nitrogen content of 12.64%. Characterization of these products encompassed elemental analysis, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), thermal gravimetric analysis (TGA), and field emission scanning electron microscopy (FESEM).